(untitled) (Altre Modernità, 2018)
One of the dominant themes of Eric Ambler’s novels of the 1930s is certainly the crossing of frontiers as both a physical and symbolic element, which results not only in the living of a nightmarish adventure but also in what spy fiction expert Michael Denning defines as ’loss of innocence’. Focusing mainly on two of Ambler’s novels, Epitaph for a Spy and Cause for Alarm, the essay analyses the experience abroad as a challenge both for the protagonists’ worldviews and for the readers’ expectations based on formula conventions. If in Epitaph for a Spy Vadassy is misled by his preconceived ideas and deductive approach, Marlow in Cause for Alarm will have to reconsider his ideas on corruption, originally attributed to the Italians, when forced to acknowledge British involvement in arms traffic in the name of business. At the same time, though, Ambler uses his characters and plots to force the formula conventions of espionage literature, presenting anti-heroes no longer driven by patriotic values and acting against their will; moreover, he introduces business as a new enemy with no frontiers, and moral dilemmas that defy easy good/bad distinctions. Using suggestions of popular literature studies, we have tried to show Ambler’s successful attempt at breaking the barriers between formulaic and mimetic fiction, through novels that possess escapist features and yet reveal a great deal of the real context of the 1930s, of which the author showed deep awareness.